IMPLICATIONS OF THE TEMPORAL DISTRIBUTION OF HIGH-MG MAGMAS FOR MANTLE PLUME VOLCANISM THROUGH TIME - Isley A.E.; Abbott D.H. (My University, 2002)
We compile a 3.7-b.yr.-long time series of ultramafic and mafic rocks including extrusives and shallow intrusives (dikes and sills). We infer that peaks in the time series represent mantle plume events. Rocks erupted from plumes are becoming more Ti rich through time, and several rock types having 1 18 wt % MgO are Phanerozoic analogs for komatiites. These include meimechites, ankaramites, and rocks previously called "picrites." Spectral analysis reveals the time series is driven by periods of similar to800 and similar to273 m. yr. Two 256-m.yr.-long data subsets, one sampling the Archean and one sampling the Phanerozoic, are driven by periods of 26 +/- 3 and 34.5 +/- 4.5 m. yr., respectively. The similar to800-m.yr.- long energy may reflect changes in the rate of impacts of extraterrestrial objects, tectonic slab cascades into the mesosphere, or resonance between free-core nutations and those forced by solar torques. We suggest that the 273 m. yr. period reflects the cosmic year. The latter modulates fluctuation in cometary impacts that occur with a 30-35 m. yr. period (Matese et al. 1996). Thus, there may be more than one driving force for mantle plume volcanism, including forces endogenic and exogenic to Earth.